2003
DOI: 10.1034/j.1600-051x.2003.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Plaque removal with a novel manual toothbrush (X‐Active) and the Braun Oral‐B 3D Plaque Remover

Abstract: A 5-week training period with repeated hands-on instruction gives panellists the skill to perform brushing with efficacy comparable to that of professional brushing. In agreement with a previous study, the 3D was more effective than a flat-trimmed manual toothbrush (Van der Weijden et al. 1994). Brushing with the criss-cross resulted in small statistical differences with the 3D and the flat-trimmed manual toothbrush. The clinical relevance of these statistically significant results should be the subject of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…In the present study, instant plaque reductions observed without dentifrice ranged between 52% and 57%. These results are not surprising because studies evaluating the plaque removal capacity of electric versus manual toothbrushing have reported already that brushing without dentifrice can be very effective 21,23‐25 . Furthermore, the present study found no differences between brushing procedures in terms of plaque reduction for the groups using dentifrices B and C. Interestingly, brushing with dentifrice A resulted in less plaque removal than brushing without this product.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, instant plaque reductions observed without dentifrice ranged between 52% and 57%. These results are not surprising because studies evaluating the plaque removal capacity of electric versus manual toothbrushing have reported already that brushing without dentifrice can be very effective 21,23‐25 . Furthermore, the present study found no differences between brushing procedures in terms of plaque reduction for the groups using dentifrices B and C. Interestingly, brushing with dentifrice A resulted in less plaque removal than brushing without this product.…”
Section: Discussionsupporting
confidence: 73%
“…Our results are in accordance with older studies,(Ramsey et al .,[17], Vander Weijden et al .,[18], Claydon et al .,[1920]), which showed the inability of the mouth wash to reach the lingual surfaces. However, in Group I, stained plaque on the lingual surfaces were greater than that on the vestibular surfaces.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, plaque reductions observed by brushing with or without a dentifrice were ‐0% and 56%, respectively. The fact that manual toothbrushing without a dentifrice can remove substantial amounts of plaque was already known from studies 6,19,21,22 evaluating the plaque‐removal capacity of electric versus manual toothbrushing. Furthermore, the outcomes from the present study are in line with the observations of a previous split‐mouth study, 12 in which the additional effect of three commercially available dentifrices on the instant efficacy of manual toothbrushing was evaluated.…”
Section: Discussionmentioning
confidence: 99%